2013
DOI: 10.1002/dc.22941
|View full text |Cite
|
Sign up to set email alerts
|

Anal cytology as a predictor of anal intraepithelial neoplasia in HIV‐positive men and women

Abstract: Human immunodeficiency virus (HIV)-infected individuals have increased risk of anal intraepithelial neoplasia (AIN) and squamous cell carcinoma (SCC). Cytologic screening is invaluable in the detection of cervical neoplasia, therefore many clinicians have adopted anal cytology as part of anal cancer screening in patients at high-risk for anal neoplasia. The purpose of this study is to determine whether anal cytology is a valuable screening test for identifying AIN in HIV+ patients. The cohort included 228 HIV+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…Anal cytology is known to underestimate the grade of AIN on biopsy; however follow-up of unsatisfactory anal Pap smears has not been extensively studied [3,10]. Unsatisfactory anal cytology rate of 17.8% in our study is similar to that reported by Morency et al [13].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Anal cytology is known to underestimate the grade of AIN on biopsy; however follow-up of unsatisfactory anal Pap smears has not been extensively studied [3,10]. Unsatisfactory anal cytology rate of 17.8% in our study is similar to that reported by Morency et al [13].…”
Section: Discussionsupporting
confidence: 86%
“…However, in people living with HIV/AIDS it is the fourth most common cancer. The incidence of anal cancer in HIV-infected MSM is estimated at 131 per 100,000 personyears and surpasses the rate of cervical cancer in women prior to the initiation of screening [3,4]. The incidence of AIN has not decreased since highly active antiretroviral therapy (HAART) therapy began [5].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of anal cytology to detect AINs of any grade ranges between 68 % by self-collection and 70 % as collected by clinicians in one report [36] and 83 % in another [37], and the sensitivity for identifying high-grade AINs is reported to be 33-39 % [36]. In HIV-positive patients, the sensitivity is as low as 20 % [38] and as high as 84 % [33]. Berry et al [39] demonstrated differences in the sensitivity of anal cytology between HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 95%
“…97 Many studies have found poor correlation between grade of the cytology report and grade diagnosed on subsequent biopsy. 46,84,97,109-111 This may reflect the difficulty of thorough anal canal cytologic sampling, the skill of the anoscopist and the inherent limitations of HRA and HRA-guided biopsy. 110,112 …”
Section: Anal Cancer Screening Methods: Strengths and Limitationsmentioning
confidence: 99%